Debt Management Performance Assessment : Kosovo - World Bank (World Bank, Washington, DC, 2020)
At the request of the Government of Kosovo (GoK), a World Bank (WB) mission visited Kosovo during September 26 to October 04, 2017 to conduct a debt management performance assessment (DeMPA). The objectives of the mission were (i) to assess the strengths and areas of development; (ii) to discuss the authorities’ immediate needs for TA and follow-up reform plan activities. This report assesses the debt management performance of the government to manage central government debt by applying the 2015 DeMPA methodology. This is the second evaluation of the government debt performances for the country. The first DeMPA assessment was conducted in 2012. Kosovo also benefitted from a Medium-Term Debt Management Strategy mission in February 2017. The mission worked with government officials from Cash and Debt Management Department (CDMD) of the Treasury, an agency of Ministry of Finance (MoF), as the main counter party. Meetings were also held with the Central Bank of Kosovo (CBK), National Audit Office (NAO), Kosovo Pension Savings Fund (KPSF), and three primary dealer banks, as well as with various units of the MoF, including human resources, legal office and internal audit. The mission agenda and the list of officials met during the mission are included in Annex 1. The main findings of this assessment along the five main areas of the DeMPA methodology are summarized below. Overall, there have been noteworthy improvements in various areas of debt management, including strategy development, domestic borrowing, debt reporting and recording. Challenges mainly arise from staffing constraints, which induce a high level of operational risk.